2016
DOI: 10.1007/s11695-016-2229-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Morbimortality in Sleeve Gastrectomy. The Importance of the Learning Curve. A Spanish-Portuguese Multicenter Study

Abstract: The safety of SG may be compromised by nonmodifiable factors such as age >65, patient comorbidities (DM2, hypertension), and prior treatment with anticoagulants, as well as by modifiable factors such as smoking, bougie size <40 F, distance to the pylorus <4 cm, and the surgeon's experience (<50-100 cases).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…The lack of adherence to follow-up was reported previously, and it can be related to several issues, including the distance to the medical office and a lack of trust or rapport with the surgeon or the medical team[46]. However, the most relevant strength of this study is that all patients underwent a standardized LSG operative technique, first, because surgeon expertise is a key issue to lower the complications rate[13,24] and second, because there were no technical differences that may influence the weight loss results. We always tried to perform a more restrictive LSG by using a thinner bougie and beginning the dissection 3 cm from the pylorus to achieve greater weight loss, as suggested by Baltasar et al[8,31].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The lack of adherence to follow-up was reported previously, and it can be related to several issues, including the distance to the medical office and a lack of trust or rapport with the surgeon or the medical team[46]. However, the most relevant strength of this study is that all patients underwent a standardized LSG operative technique, first, because surgeon expertise is a key issue to lower the complications rate[13,24] and second, because there were no technical differences that may influence the weight loss results. We always tried to perform a more restrictive LSG by using a thinner bougie and beginning the dissection 3 cm from the pylorus to achieve greater weight loss, as suggested by Baltasar et al[8,31].…”
Section: Discussionmentioning
confidence: 93%
“…However, LSG can be a very difficult procedure even for laparoscopic surgeons with advanced skills. The surgeon’s experience and some technical aspects, such as the bougie size (less than 40 F) and the distance to the pylorus being less than 4 cm from the first stapling, have been previously reported as risk factors for the development of complications after a LSG[13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this increase is multi-factorial. It is perceived as a less technically demanding procedure to perform and to learn [ [11] , [12] , [13] , [14] ] although two recent studies have suggested the true learning curve may be up to 100 cases [ 45 , 46 ]. LSG avoids the need for intestinal anastomosis and allows full endoscopic access to the duodenum and biliary tree after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Una posible explicación seria que el presente trabajo solo consideró pacientes con comorbilidades (DM2, dislipidemia, hipertensión arterial) independientemente del tipo de obesidad. Sanchez et al (33) encontraron que algunos de estos factores como diabetes condicionan peores resultados ponderales de los pacientes sometidos a cirugía bariátrica.…”
Section: Agradecimientosunclassified